Afterslip and viscoelastic relaxation following the 2011 Tohoku-oki earthquake (Mw9.0) inferred from inland GPS and seafloor GPS/Acoustic data - Yamagiwa, Shuji; Miyazaki, Shin'ichi; Hirahara, Kazuro; Fukahata, Yukitoshi (Geophysical research letters, 2015)
We simultaneously estimate 2.5 years of afterslip and viscoelastic relaxation, as well as coseismic slip, for the 2011 Tohoku‐oki earthquake. Displacements at inland GPS and seafloor GPS/Acoustic stations are inverted using viscoelastic Green's functions for a model with an upper elastic layer and lower viscoelastic substrate. The result shows that afterslip is isolated from the rupture area and possibly asperities of historical earthquakes and has almost decayed by 10 September 2013, 2.5 years after the main shock. The inversion result also suggests that observed landward postseismic displacements at the seafloor GPS/Acoustic stations are caused by the viscoelastic relaxation, whereas trenchward displacements at inland stations are mainly an elastic response to afterslip. Key Points A coupled afterslip and viscoelastic relaxation model fits postseismic data Viscous flow induces landward motions at GPS/A stations above the rupture area Afterslip in the downdip extension of the rupture area has decayed in 2.5 years